ANALYSIS OF LOTS AND HOTS QUESTIONS ON SOUTH SUMATRA LOCAL HISTORY IN HIGH SCHOOL TEXTBOOKS: Analisis soal- soal LOTS dan HOTS Pada Materi Sejarah Lokal Sumatera Selatan Dalam Buku Teks SMA - SARTIKA; Sukardi; Nur Syafarudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Developing Lower-Order Thinking Skills (LOTS) and Higher-Order Thinking Skills (HOTS) is a crucial objective of history education. However, studies analyzing LOTS and HOTS questions regarding the local history of South Sumatra across various curricula remain limited. Therefore, this study aims to analyze the characteristics of LOTS and HOTS questions in high school history textbooks. A qualitative descriptive method employing a content analysis approach was used. Data were collected through observation, interviews with history teachers, and an examination of history textbooks from the 2009 Curriculum, the 2013 Curriculum, and the Kurikulum Merdeka (Independent Curriculum). The findings indicate that the questions span cognitive levels C1 through C6, based on Anderson and Krathwohl’s Revised Bloom’s Taxonomy. The 2009 Curriculum contained two LOTS questions and two HOTS questions; the 2013 Curriculum consisted entirely of six HOTS questions; and the Kurikulum Merdeka included two LOTS questions and five HOTS questions. These results demonstrate that the 2013 Curriculum and the Kurikulum Merdeka place greater emphasis on higher-order thinking than the 2009 Curriculum. This study offers practical implications for history teachers and textbook developers regarding the design of local history assessment questions that foster students' critical and analytical thinking skills.